POLA MANAJEMEN HKI PT. TROPICA NUCIFERA INDUSTRY SEBAGAI STRATEGI PENGEMBANGAN USAHA DAN TEROBOSAN CERDAS MEMBINA KEMITRAAN DENGAN INSTANSI PEMERINTAH - , Shaum Shiyan., S.Farm ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The study entitled âThe Pattern of Intellectual Property Rights (IPR) Management at PT. Tropica Nucifera Industry as a Strategy of Bussiness Development and Smart Breakthrough to Develop Partnership with Goverment Resortâ, has been done. Itâs an interesting phenomenon that creativity will match with IPR. Intelligence to gain the partnership with stakeholder is breakthrough in a business. The expectation is to achieve a great yet economic challenge. The aims of this qualitative study is understanding about the pattern of intellectual property and IPR at PT. TNI. Understanding on the strategy of bussiness development. Besides that is to understand about intellectual property management to gain the partnership with goverment resort. The method to collect the data were used interview method, observation, documentation and library study. Sampling method as a data resource were used purposive sampling and snowball sampling. The result is PT. TNI could not manage intellectual property in a strong IPR management. The sistematic pattern of IPR at PT. TNI have not seen yet. Strategy of bussiness development have smooth and simplicity impression. It means, with limited resources PT. TNI try to approach with potential ousiders to support bussiness progression. The result is competitive advantage could be created on the competition. Partnership with goverment and the society through the effort of integreted coconut manufacturing is a form of creative breakthrough in order to improve the chance in business.